PEMETAAN GEOLOGI STRUKTUR UNTUK MENENTUKAN GAMBARAN TEKTONIK DAERAH KAWENGEN DAN SEKITARNYA, KECAMATAN UNGARAN TIMUR, KABUPATEN SEMARANG - Christian Widiasmoro Putro (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
Research area is located on the border of two district, there are district of Semarang and Demak which includes the village of Kawengen, Penawangan, and surrounding areas, subdistrict of East Ungaran and the village of Barang, subdistrict of Mranggen. The mean of this research is to determine the tectonic overview of Kawengen and the surrounding area, in with the purpose are to find out geological structure of fold, fault, and joint that formed in research area, know the pattern of the geological structure, know the mechanism and main trend direction forming the geological structure, know the time of forming of geological structure, know the relationship between of the geological structure formed with tectonic history in research area.The collecting of data was done by mapping of semidetail geological structure and continued with processing and analyzing of data. The analysis were lineament pattern of topographic map and image of DEM analysis, stereographic analysis, and determination of relative age of rocks analysis.Litology units that forming the Kawengen area started from the youngest to the oldest are claystone interbeded sandstone unit, claystone – sandstone unit, limestone unit, carbonate sandstone unit, tufaceous sandstone unit, lava breccias unit, and volcanic breccias unit.The geological structures that formed in research area are folds, faults, and joints which the main direction are west – east, north - south, and northwest – southeast. From the stereographic analysis, main direction that form the geological structure are northwest – southeast, north – south, southwest – northeast. The making of geological structures in Kawengen were occurred in phase of inversion structure that the extension structures turned into a compression structure which resulted of the subduction of Australian plate and Eurasian plate. The geological pattern of Kawengen area are indicated as imbricate fault type which is associated with the folds (fault propagation fold). The making of the fault is also related to the establishment of strike slip fault in research area. Tectonic history in Kendeng zone started from Last Oligocene – Middle Miocene that caused the existing structure inverted. It was the result of the compression tectonic regime. This compression phase continued in the Middle Miocene – Last Miocene and last occurred in the Last Pliocene - Early Pleistocene.